Pancreatic neuro-insular network in young mice revealed by 3D panoramic histology - Tang, Shiue-Cheng; Shen, Chia-Ning; Lin, Pei-Yu; Peng, Shih-Jung; Chien, Hung-Jen; Chou, Ya-Hsien; Chamberlain, Chester E.; Pasricha, Pankaj J. (Diabetologia, 2018)
Aims/hypothesis It has been proposed that the neuro-insular network enables rapid, synchronised insulin secretion. However, to date, acquiring the pancreatic tissue map to study the neural network remains a challenging task as there is a lack of feasible approaches for large-scale tissue analysis at the organ level. Here, we have developed 3-dimensional (3D) panoramic histology to characterise the pancreatic neuro-insular network in young mice. Methods Pancreases harvested from young wild-type B6 mice (3 and 8 weeks old) and db / db mice (3 weeks old; db / db vs db /+) were used to develop 3D panoramic histology. Transparent pancreases were prepared by optical clearing to enable deep-tissue, tile-scanning microscopy for qualitative and quantitative analyses of islets and the pancreatic tissue network in space. Results 3D panoramic histology reveals the pancreatic neurovascular network and the coupling of ganglionic and islet populations via the network. This integration is identified in both 3- and 8-week-old mice, featuring the peri-arteriolar neuro-insular network and islet–ganglionic aggregation. In weaning hyperphagic db / db mice, the 3D image data identifies the associated increases in weight, adipose tissue attached to the pancreas, density of large islets (major axis > 150 μm) and pancreatic sympathetic innervation compared with db /+ mice. Conclusions/interpretation Our work provides insight into the neuro-insular integration at the organ level and demonstrates a new approach for investigating previously unknown details of the pancreatic tissue network in health and disease.